2009
DOI: 10.1371/journal.pone.0006032
|View full text |Cite
|
Sign up to set email alerts
|

A Trivalent Virus-Like Particle Vaccine Elicits Protective Immune Responses against Seasonal Influenza Strains in Mice and Ferrets

Abstract: There is need for improved human influenza vaccines, particularly for older adults who are at greatest risk for severe disease, as well as to address the continuous antigenic drift within circulating human subtypes of influenza virus. We have engineered an influenza virus-like particle (VLP) as a new generation vaccine candidate purified from the supernatants of Sf9 insect cells following infection by recombinant baculoviruses to express three influenza virus proteins, hemagglutinin (HA), neuraminidase (NA), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 33 publications
2
60
0
Order By: Relevance
“…Until now, production of insect cell derived influenza VLP vaccines has been carried out in Sf9 cells [13][14][15][16][17][18][19][20]. We conclude from our results that BTI-TN5B1-4 cells are an advantageous production system for influenza VLPs as it decreases the baculovirus background and therefore DNA contamination.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Until now, production of insect cell derived influenza VLP vaccines has been carried out in Sf9 cells [13][14][15][16][17][18][19][20]. We conclude from our results that BTI-TN5B1-4 cells are an advantageous production system for influenza VLPs as it decreases the baculovirus background and therefore DNA contamination.…”
Section: Discussionmentioning
confidence: 73%
“…VLPs of influenza subtypes H1, H3, H5 and H9 have been generated in insect cells by co-expression of HA, NA, M1 and M2 or HA, NA and M1 or by co-expression of HA and M1, respectively [13][14][15][16][17][18][19][20]. Immunological studies with all of these subtypes have shown superior immune responses against influenza A when administered intranasally, intraperitoneally or intramuscularly [11,[13][14][15][16][17][18]20]. Up to date all of these studies have been carried out with VLPs that had been produced in the Spodoptera frugiperda insect cell line Sf9.…”
Section: Introductionmentioning
confidence: 99%
“…Virus-like particles (VLPs) have been suggested as a promising candidate vaccine against influenza viruses. Such influenza VLPs have been demonstrated to provide protective immunity in experimental animal models (12,15,19,37,44), and VLP vaccines against other diseases are in widespread clinical use (18).…”
mentioning
confidence: 99%
“…Influenza VLP vaccines have been shown to induce protection, suggesting that VLPs can be a promising vaccine candidate (2,7,10,12,29,31,34). Immune responses after mucosal immunization are relatively low (32).…”
Section: Discussionmentioning
confidence: 99%